IDENTIFICATION OF MARINE DEBRIS ON MARANNU BEACH PASIMARANNU VILLAGE, SINJAI REGENCY - Andi Nurzakilah Putri Cempaka; Fatma Fatma (Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
Marine debris has become one of the most significant environmental challenges affecting coastal ecosystems, particularly in developing coastal regions where fisheries, tourism, and human settlements coexist. This study aimed to identify the composition, size distribution, biomass, and spatial distribution of marine debris on Marannu Beach, Pasimarannu Village, Sinjai Regency. Field sampling was conducted in May 2025 using the line transect method recommended by NOAA. Three sampling stations were established, each consisting of three transects and three 10 × 10 m quadrats. All collected debris was classified according to material type (plastic, wood, glass, rubber, textile, metal, and expanded polystyrene), size category (mega, macro, and meso), and total weight. Oceanographic parameters, including currents, waves, and tides, were obtained from the Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG) to support interpretation of debris accumulation patterns. The results demonstrated that plastic was the dominant debris type at all sampling stations, reflecting the substantial influence of fisheries, tourism, and domestic activities on coastal pollution. Macro-debris represented the predominant size category, indicating that most waste entered the coastal environment before undergoing fragmentation. In contrast, wooden debris contributed the greatest biomass despite being less abundant than plastics. Variations among sampling stations were closely associated with differences in surrounding land use and hydrodynamic conditions, particularly current direction, wave height, and tidal fluctuations. These findings indicate that marine debris accumulation on Marannu Beach is controlled by the interaction between anthropogenic activities and oceanographic processes. Therefore, integrated coastal waste management, continuous environmental monitoring, community participation, and improved solid waste management systems are essential to reduce marine debris pollution and support sustainable coastal ecosystem conservation.